Logistics & Supply Chain Management - Christopher, Martin (Pearson, 2023)
"The intention behind this book, since its first edition, has always been to explore the ways in which organisations can better serve their customers and in so doing, improve the value they create. As markets become more competitive and the level of uncertainty increases, the challenge is how to develop a supply chain strategy that is capable of adapting to constantly changing conditions. Pandemics, geo-political events, trade wars and supply chain disruptions have characterised the recent past - demanding a much greater degree of flexibility and agility on the part of companies as they seek to respond to these potential threats. A further significant change that organisations must contend with today is the growing complexity of their supply chains. This has partly arisen as a consequence of outsourcing activities that were previously performed in-house, resulting in a much higher level of interdependencies across the supply/demand ecosystem. This increase in complexity makes the need for effective supply chain management even more critical than before. Hopefully the ideas presented in this book will assist both students and practitioners in their search for better ways to understand and manage supply chains in this age of uncertainty"--